Pemeriksaan Gula Darah sebagai Upaya Deteksi Dini dan Pencegahan Diabetes - EE Lailatul Putri; Muhammad Farhan; Farhan Dwi Ramadhani; Fina Dwi Apriyanti; Allysa Regina Rosa Bangun; Susi Handayani Riskiah; Mega Lestari; Cahyo Eko Prasetyo; Shafa Rafida Ghalia; Alam Anbari; Neli Murniasih; Gerald Angelo Pantarego; Anjar Pambudi; Yahadi Darman; Euginia Aurilie Putri; Salsabila Kasih Putri Ramadhani; Azmi Annisa Islamyah; Wulan Febriyanti; Ayu Wulandari; Huda Fauziyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes Mellitus (DM) is a non-communicable disease that is currently a major public health problem in Indonesia. The prevalence of DM continues to increase from year to year, not only in urban areas but also increasingly found in rural areas. One factor contributing to the high number of DM cases is a lack of public awareness of the importance of a healthy lifestyle, as well as the continued presence of many undiagnosed cases, resulting in delayed treatment. Therefore, early detection efforts and health education that can reach the community at the community level are needed. This community service program was designed to conduct random blood sugar screenings while increasing the knowledge of residents of RW 15 Kalibaru regarding the prevention and control of DM. The activity was carried out on August 24, 2025, involving 21 participants, most of whom were from adults to the elderly. The activity method consisted of two main stages: checking blood sugar levels using a glucometer and a health education session on a healthy lifestyle, a balanced diet, and the importance of regular physical activity. The results of the activity showed that the indicators of success were well achieved. This was indicated by the orderly implementation of the examinations, a high level of participation from residents, and increased awareness of the dangers of DM among participants. From the examination results, most participants had normal blood sugar levels, but several people were found with blood sugar levels above the normal limit who required medical follow-up.